Legal assistance agencies for children as criminal action victims in criminal justice processes - Dewi Athirah Aksan; M Said Karim; Abd Asis (Jurnal Cakrawala Hukum, 2020)
Children who need special protection if they are in an environment full of violence or tend not to care. The legal aspects of child protection need to be considered because legal protection of children and juvenile justice is one way to protect children in their future growth. Cases of violence against children are rife in Indonesia, namely acts of violence such as abuse, harassment and acts of sexual violence. This type of research is normative-empirical legal research at the Makassar Legal Aid Institute, the Indonesian Women's Association for Legal Assistance for Makassar Justice, the HARS Legal Aid Institute, and the Law Faculty Consultation and Legal Aid Unit at Hasanuddin University. The data source of this research is primary data from interviews and secondary data from literature studies, namely collecting data and legislation, books of scientific work, and opinions of experts. The study uses quantitative data analysis by combining secondary data obtained from literature. The results of this study concerning the forms of legal aid provided by LBH for children as victims included sociological assistance, monitoring of hearings in the court, and diversion assistance. While the optimization of services provided by LBH in handling children dealing with the law in this case the victim's child has not been effective.How to cite item: Aksan, D., Karim, M., Asis, A. (2020). Legal assistance agencies for children as criminal action victims in criminal justice processes. Jurnal Cakrawala Hukum,11(3). 313-322. doi:10.26905/idjch.v11i3.4249.